Intensitas Modal Perusahaan dan Tax Avoidance pada Perbankan Nasional - Erma Wulan Sari; Rihan Mustafa Zahri (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study aims to examine the effect of capital intensity ratio, firm size and institutional ownership on tax avoidance practices. The dependent variable used in this study is tax avoidance, while the independent variables used are capital intensity ratio, firm size and institutional ownership. The population in this study are banking companies listed on the IDX in 2016-2020. While the sampling technique in this study is purposive sampling obtained a total sample of 32 companies. The data analysis technique in this research is using multiple regression analysis. The results showed that capital intensity rtaio had an effect on tax avoidance, while firm size and institutional ownership had no effect on tax avoidance